Impact of active to inert shielding gas transition on the corrosion behavior of wire arc additively manufactured duplex stainless steel - Elina Akbarzadeh Chiniforoush; Tahereh Gholizadeh; Mohammad Reza Jandaghi; Johan Moverare; C.Hakan Gür (Materials & Design)
This study systematically examined the effects of inert (pure argon) and active (argon + 2 wt% oxygen) shielding gases on the corrosion behavior of wire arc additively manufactured (WAAM) duplex stainless steel (DSS), named ArP and ArO. Active shielding gases are commonly used in arc welding to enhance arc stability and efficiency, which prompted their selection in this study. Adding 2 % oxygen introduced ∼ 0.1 % oxygen into ArO, with thermodynamic simulations suggesting potential spinel phase formation but microstructural analyses revealed more complex oxide inclusions in ArO, reducing surface homogeneity and increasing intragranular and secondary austenite formation. Kernel Average Misorientation (KAM) analysis indicated higher residual strain in these areas. Electrochemical tests, including Open Circuit Potential (OCP), Electrochemical Impedance Spectroscopy (EIS), and Potentiodynamic Polarization, demonstrated superior corrosion resistance in ArP, with higher OCP (+73 mV), corrosion potential (+39 mV), and significantly lower corrosion current density (13 μA/cm2 vs. 49 μA/cm2), leading to ∼ 3 times greater corrosion resistance. This improvement is attributed to ArP’s thicker, less defective passive layer (87.3 nm vs. 14.0 nm). Corroded surface morphology indicated selective dissolution of δ-ferrite phase and likely pitting around inclusions. These findings highlight that active shielding gas in WAAM deteriorates the corrosion resistance of DSS.